Effects of Coenzyme Q10 Supplementation on Exercise Performance and Markers of Oxidative Stress in Hemodialysis Patients: A Double-Blind Placebo-Controlled Crossover Trial. (November 2016) - Gokbel, Hakki; Turk, Suleyman; Okudan, Nilsel; Atalay, Huseyin; Belviranli, Muaz; Gaipov, Abduzhappar; Solak, Yalcin
Abstract : Coenzyme Q10 (CoQ10) supplementation has been shown to decrease oxidative stress in a number of clinical settings. However, there are mixed results regarding the role of CoQ10 supplementation on exercise performance. Chronic kidney disease is recognized as an inflammatory state, and hemodialysis patients have low level of exercise performance. We aimed to evaluate the effect of CoQ10 supplementation on oxidative stress markers and exercise performance measures. This was a prospective, double-blind, placebo-controlled, crossover study in which all patients received placebo and oral CoQ10 200 mg/d. Participants underwent 6-minute walking test and cycle ergometer. Blood samples were drawn to determine malondialdehyde, oxidized low-density lipoprotein, superoxide dismutase, and glutathione peroxidase. Walking distance in 6-minute walking test and estimated maximal oxygen consumption (VO2max ) were recorded. Twenty-eight patients were randomized, but 23 patients completed the study protocol. Serum CoQ10 level significantly increased with supplementation compared with basal values ( P < 0.05). Neither walking distance nor estimated VO2max was different between the placebo and CoQ10 groups ( P > 0.05). Serum malondialdehyde levels significantly increased in both groups compared with baseline values just after the exercise ( P < 0.05). There was no difference in markers of oxidative stress and antioxidant system between placebo and CoQ10 supplementation with exercise ( P > 0.05). The results of this study showed no significant effect of CoQ10 supplementation on exercise performance measures and oxidative system markers compared with placebo in maintenance hemodialysis patients.